Porównanie postaw przedsiębiorczych studentów studiów ekonomicznych, społecznych i humanistycznych - Dąbrowska, Karolina; Skowron, Mariusz (Annales. Etyka w Życiu Gospodarczym, 2015)
Success in economic life is a result of the interaction of many factors, which in different ways are developed from the individual characteristics of the person, a specific way of thinking and the ability to perceive oneself in the future. At the same time, more and more attention is focused on the influence of the entrepreneurial characteristics of individuals on their career development and career building process. The impact of personal experience on the perception of individual chances on the labour market is also emphasized. The purpose of this paper is, therefore, to identify the differences in enterprising attitudes of students of the humanities and students of economics, as well as compare the characteristics of entrepreneurial abilities between both student groups on the basis of empirical research conducted among students at the University of Lodz.